Pemilihan Calon Karyawan Dengan Metode SAW Pada Griya Adventure - Hasman Budiadi; Adensa Frynanda Ramadika; Setiyowati (STMIK Amik Riau, 2024)
Griya Adventure is a distributor that provides various sports equipment such as mountain climbing and rock climbing equipment. Increasing customer orders requires additional employees. The Griya Adventure employee recruitment process currently does not use a system, the process is carried out through several stages, namely administrative selection, psychological tests, interviews and work experience. HRD experiences difficulty in determining the best employee candidates, so a decision support system is needed to accept the best employee candidates. This research aims to create a decision support system for recruiting prospective employees at Griya Adventure that is able to produce the best decisions. System development uses the Waterfall method, while the decision making method uses Simple Additive Weighting (SAW). The criteria used are (1) Administrative Selection, (2) Psychological Tests, (3) Interviews, (4) work experience. System testing uses Black Box Test. The result is a system that is able to provide recommendations in the form of ranking the best prospective employees. Black Box testing results show that the system functions well, without errors. The validity test shows that the overall results are valid.